Sintomatología depresiva, actitudes disfuncionales, perfeccionismo y auto-concepto en un grupo de adolescentes puertorriqueños (Revista Puertorriqueña de Psicologia, 2016)
Depression is a serious mental disoreder among Puerto Rico children and adolescents. Scientific literature have identified irrational beliefs, negative self-concept and perfectionism as variables significatively associated with depression. The aim of this study was to understand depression and cognitions related among Puerto Rican adolescents. A community sample of 309 adolescents between 14 and 18 years was evaluated. Measures ot rate depressive symptomatology, self-concept, irrational beliefs and perfectionism were administered. Statistical analysis revealed a significative relationship between depressive sypmtomatology and dysfunctional attitudes (r=.469)